Long‐term outcomes and cost effectiveness of high‐dose dexamethasone for cardiac surgery: a randomised trial. (20th March 2017) - Dieleman, J. M.; de Wit, G. A.; Nierich, A. P.; Rosseel, P. M.; van der Maaten, J. M.; Hofland, J.; Diephuis, J. C.; de Lange, F.; Boer, C.; Neslo, R. E.; Moons, K. G.; van Herwerden, L. A.; et al.
Summary: Prophylactic intra‐operative administration of dexamethasone may improve short‐term clinical outcomes in cardiac surgical patients. The purpose of this study was to evaluate long‐term clinical outcomes and cost effectiveness of dexamethasone versus placebo. Patients included in the multicentre, randomised, double‐blind, placebo‐controlled DExamethasone for Cardiac Surgery (DECS) trial were followed up for 12 months after their cardiac surgical procedure. In the DECS trial, patients received a single intra‐operative dose of dexamethasone 1 mg.kg −1 (n = 2239) or placebo (n = 2255). The effects on the incidence of major postoperative events were evaluated. Also, overall costs for the 12‐month postoperative period, and cost effectiveness, were compared between groups. Of 4494 randomised patients, 4457 patients (99%) were followed up until 12 months after surgery. There was no difference in the incidence of major postoperative events, the relative risk (95%CI) being 0.86 (0.72‐1.03); p = 0.1. Treatment with dexamethasone reduced costs per patient by £921 [€1084] (95%CI £−1672 to −137; p = 0.02), mainly through reduction of postoperative respiratory failure and duration of postoperative hospital stay. The probability of dexamethasone being cost effective compared with placebo was 97% at a threshold value of £17, 000 [€20, 000] per quality‐adjusted life year. We conclude that intra‐operative high‐dose dexamethasone did not have an effect on major adverse events at 12 months after cardiac surgery, but was associated with a reduction in costs. Routine dexamethasone administration is expected to be cost effective at commonly accepted threshold levels for cost effectiveness.